Avaliação da função autonômica cardíaca e sua relação com a capacidade funcional em pacientes com DPOC - Bonança, Adriana Mazzuco (Universidade Federal de São Carlos, 2015)
In chronic obstructive pulmonary disease (COPD), functional and structural impairment of lung function can negatively impact heart rate variability (HRV); in addition, a reduced exercise capacity is an important independent prognostic marker in COPD patients. However, 1) if the degree of lung impairment negatively impacts HRV responses and 2) whether the injury of the autonomic control may be associated with reduced exercise capacity in patients with COPD remain unclear. Thus, two studies were conducted in order to verify if functional status at rest and during exercise would be related to autonomic impairment in COPD patients. In the first study, entitled "Relationship between linear and nonlinear dynamics of heart rate and impairment of lung function in COPD patients," we investigated whether the impairment static lung volumes and lung diffusion capacity (DL) would be related to HRV indices in moderate-to-severe COPD. Sixteen patients with COPD underwent pulmonary function tests (spirometry, plethysmography and lung diffusion capacity for carbon monoxide - DLCO). The RR interval was registered in the supine, standing and seated positions and during a respiratory sinus arrhythmia maneuver (M-RSA). Our results suggest that responses of HRV indices were more prominent during M-RSA in moderate-to-severe COPD. Moreover, greater lung function impairment was related to poorer heart rate dynamics. Finally, impaired DLCO is related to an altered parasympathetic response in these patients. The second study, entitled "Are linear and nonlinear heart rate dynamics in submaximal exercise related to cardiorespiratory responses during maximal exercise in patients with COPD?", we inquired whether there is a relationship between HRV responses and exercise capacity in patients with COPD. Fifteen patients underwent incremental cardiopulmonary exercise testing and six-minute walk test (6MWT). The RR interval was registered at rest (standing position) and during 6MWT. Our results showed that HRV responses at rest and during simple field tests may reflect functional impairment of COPD patients, providing important information about both ventilatory and hemodynamic inefficiency in these patients.
Keywords: Doença Pulmonar Obstrutiva Crônica (DPOC); Variabilidade da frequência cardíaca; Teste de caminhada; Teste de exercício cardiopulmonar; Capacidade de difusão pulmonar; Static lung volumes; Lung diffusion capacity; Cardiopulmonary exercise testing; Cardiac autonomic nervous system; Heart rate variability; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL